Producing Participants: Trustworthiness as Convenient Fiction - Van Cleave, Jessica; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Objectivity (philosophy); Qualitative research; Quality (philosophy); Reputation; Rigour; Transparency (behavior); Trustworthiness; Verisimilitude; dept.cur; fiction; methodologies; qualitative criteria; qualitative research; transparency; trustworthiness

Purposeful Entanglements: A New Materialist Analysis of Transformative Interviews - Marn, Travis M.; Wolgemuth, Jennifer R. (Qualitative Inquiry, 2017)
In this article, we explore transformative interviewing through the lens of new materialism. Rather than viewing transformation through a humanist perspective that centralizes a transcendent self, we draw upon Barad’s agential realism to reconsider transformation following the ontological turn. Thinking with agential realism, we engaged two interview studies, one on biracialism and one on masculinity, to demonstrate how the materiality of our interviews (e.g., research bodies, computer programs, questionnaires) intra-acted with our participants to both facilitate and hinder our attempts at transformation. We conclude by theorizing transformation as a type of purposeful entanglement that proceeds from the material-discursive intra-actions of our inquiries.
Keywords: dept.cur

Adoptive Parents’ Suspicion and Coping With the Possibility of Child Abduction for International Adoption in China - Marn, Travis M.; Tan, Tony Xing (The Family Journal, 2015)
In this study, we investigated (1) whether adoptive parents suspected their children might have been victims of abduction for adoption in China and (2) for parents who were uncertain if their own children might be victims of child abduction for adoption, how they coped with the possibility. A total of 342 adoptive parents (representing 529 adopted Chinese children) completed an anonymous online survey on their experiences. Of the 342 parents, 154 (45%) described how they coped with the possibility that their children might be the victims of child abduction for adoption. In terms of suspicion, we found that for about 70% of the children, the parents responded Never; for 18.5% of the children, the parents responded Rarely; for 11.7% of the children, the parents responded Sometimes; and for about 1% of the children, the parents responded that they Always suspected that their children might be victims of abduction for adoption. In terms of coping with the possibility that their children might have been victims of child abduction for adoption, thematic analysis on the 154 parents’ descriptions revealed that parents experienced one or more of seven emotional reactions: sadness, frustration/helplessness, complicity/guilt, anger, fear/worry, hypervigilance, resolve, as well as the belief that they were not affected. Finally, we discussed contributing factors to child abduction for adoption and to adoptive parents’ suspicion of such a practice.
Keywords: dept.cur

Biracial Place Walkers on Campus: A Trioethnography of Culture, Climate, and Currere - Agosto, Vonzell; Marn, Travis; Ramirez, Rica (International Review of Qualitative Research, 2015)
Send this e-mail to Rica and Travis: Rica and Travis, I wish you could have been at the duoethnography panel. The first presentation had some uneasy conversations. The second, Dr. Colomer's presentation, was cool: A performance with guest actors had some sad moments with death, health issues, and attrition. The next presentation was about miscarriage and grief counseling. I wondered if our paper is frivolous in comparison to the others. I think not. Our episodes of cultural starvation and indifference are there and painful, but our comebacks are so quick (nourishment as resistance), and therefore so is the celebration. Written by Agosto while flying home after presenting at the 2014 International Congress of Qualitative Inquiry.
Keywords: dept.cur

The failures and possibilities of philosophy in the material world - Van Cleave, Jessica; Marn, Travis; Wolgemuth, Jennifer (International Review of Qualitative Research, 2025)
Keywords: Engineering; Engineering ethics; Epistemology; Philosophy; dept.cur

Manufacturing Trustworthiness in Qualitative Research as a Writerly and Readerly Accomplishment: Introduction to the Special Issue - Van Cleave, Jessica; Wolgemuth, Jennifer; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Construct (python library); Product (mathematics); Qualitative research; Space (punctuation); Theme (computing); Tinker; Trustworthiness; dept.cur; possibility; publication; scholarly writing; trustworthiness

On the sidelines of what works: scientifically based indifference - Wolgemuth, Jennifer R.; Marn, Travis M.; Sabnis, Sujay (International Journal of Research & Method in Education, 2021)
A team of systematic reviewers successfully completed a government-commissioned review of ‘what works to improve post-school outcomes for youth with disabilities’ in 2012. Despite its success, interviews with 10 review team members revealed dissatisfaction with the process and indifference to its outcomes. The purpose of our analysis was to examine how the systematic review process itself led to review team members’ feelings of indifference, resignation, and pessimism. Drawing on the writings of Henry Giroux, Gert Biesta, and Hanna Arendt that warn of the death of democracy and the rise of totalitarianism, we explored how the systematic review certification process, examinations, rules, and structures deadened democratic deliberation and critique necessary, we argue, to conducting good educational science. We end with a call for systematic reviews in education whose researchers, products, and processes remain ethically oriented to keeping democracy alive. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
2 citations (Crossref) [2023-10-31]
Keywords: dept.cur; peer-reviewed

New materialism: An end to certainty - Marn, Travis; Cleave, Jessica Van (Theory and Philosophy in Qualitative Research Methods: Key Concepts, 2026)
The purpose of this entry is to provide an orientation to new materialism, a form of inquiry or philosophy that brings renewed interest to materiality. New materialist philosophies offer an end to certainty, an end to the belief that meaning, knowledge, and agency are fixed and stable. New materialism, however, is not a cohesive body of work but rather a collection of theories, theorists, works, and assumptions, each with its own goals, methods, and desired end points. What constitutes new materialism, what contributes to new materialism, and what inspires new materialist scholarship are not necessarily the same. We trace some of the historical influences of new materialism, highlighting key theories and theorists, describing the intersecting philosophical traditions that mutually constitute new materialism, and exploring the implications of new materialism both for social justice and for qualitative research. © 2026 selection and editorial matter, Aaron M. Kuntz; individual chapters, the contributors.
Keywords: dept.cur

Implicit Attitudes of International and American Adult Students toward Black and White Teachers - Na, Eunkyung; Tan, Tony X.; Marn, Travis; Ramirez, Rica (Commission for International Adult Education, 2015)
The purpose of this study was to examine hidden prejudice in two groups of adult students, international and American, against black compared to white teachers. Social desirability in the minds of participants may affect the result of a study involving racial bias (Mullins, 1982). For this reason, the researchers created a computer protocol using the standard Implicit Association Test (IAT) to measure the implicit attitudes of participants. The IAT relies on the idea of automatic information process within the mind that is not impacted by social desirability. A clear concern in education is that the racial bias toward minority students will let those implicit biases affect the way they teach those students, creating a self-fulfilling prophesy of poor student performance. But the implicit bias can work both ways and can impact a teacher's effectiveness. Traditional racial prejudice theories usually looked at white's attitudes toward blacks and other groups. This study had a significant directional shift by focusing on the international students' racial attitudes toward black and white teachers. The implicit racial attitudes of international students were also compared to those of American students. The result and evaluation of this study may be a valuable tool to improve student services and teacher professional development in higher education. Suggestions for future research are also provided.[For full proceedings, see ED570489.]
ERIC Number: ED570505
Keywords: Adult Students; African American Teachers; Attitude Measures; College Students; Comparative Analysis; Foreign Students; Gender Differences; Racial Attitudes; Racial Bias; Social Desirability; Statistical Analysis; Student Attitudes; Surveys; Whites; dept.cur

#scholar #famous #monster - Wolgemuth, Jennifer; Lester, Jessica; Guyotte, Kelly; Koro‐Ljungberg, Mirka; Marn, Travis (Educational Researcher, 2025)
Academic success is now coupled with social media engagement. Social media has become so normalized in the academy that absent a carefully curated social media presence, scholars risk being seen as unscholarly, unproductive, and unpopular. This article lays bare the pressures, mechanisms, and monstrosities of using social media to promote scholarship. We argue that the widespread adoption of social media outpaces critical attention to its ethics and wonder about the future of public scholarship and the monstrous scholarly selves we are becoming. Thinking of monstrosity, with Krecˇicˇ and Žižek, as the preontological domain that rests beneath society and constitutes alterity and otherness, we ask what kinds of #scholarfamousmonsters we want to be, become, and promote in the digital era.
Keywords: Aesthetics; Art; Epistemology; Law; Literature; Media studies; Monster; Philosophy; Political science; Psychology; Scholarship; Social media; Social psychology; Sociology; Wonder; dept.cur; peer-reviewed

Start here, or here, no here: introductions to rethinking education policy and methodology in a post-truth era - Wolgemuth, Jennifer R.; Koro-Ljungberg, Mirka; Marn, Travis M.; Onwuegbuzie, Anthony J.; Dougherty, Shaun M. (Education Policy Analysis Archives, 2018)
This special issue takes up urgent questions about how we education scholars might think and do policy and methodology in what has come to be known as the post-truth era. The authors in this special issue grapple with questions about the roles and responsibilities of educational researchers in an era in which research and policy have lost their moorings in T/truth. Collectively they reconceptualize educational research and policy in light of post-truths, anti-science sentiment, and the global rise of right-wing populism. At the same time we editors wonder whether post-truth is given a bad rap. Could post-truth have something productive to offer? What does post-truth open up for educational research and policy? Or, is the real issue of this special issue a collective despair of our own insignificance and obsolescence in the wake of post-truth. Whatever we editors and authors aimed to do, this special issue will not be heard by post-truth adherents and partisans. Perhaps its only contribution is encouragement to stay with the troubles of a post-truth era, even as we despair the consequences of our research and policy creations. © 2018, Arizona State University. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00129 tex.type: [object Object]
Keywords: Education policy; Fake news; Methodology; Post-truth; dept.cur; peer-reviewed

Work/Think/Play/Birth/Death/Terror/Qualitative/Research - Wolgemuth, Jennifer R.; Rautio, Pauliina; Koro-Ljungberg, Mirka; Marn, Travis M.; Nordstrom, Susan; Clark, Adam (Qualitative Inquiry, 2018)
Inspired by work/think/play in qualitative research, we centered the idea of “play” in a qualitative research project to explore what proceeding from the idea of work/think/play might look like and accomplish. We pursued play in an experimental qualitative inquiry over dinner one night at the 2016 Annual Meeting of the American Educational Research Association. Our article centers on one work/think/play inquiry three of us conducted. Through a playful account of how play unfolded in our work/think/play inquiry that evening, we explore research play as generative, deadly, and censored in the context of neoliberalism and other terrors. We reflect on what (good) play does in qualitative research, what our work/think/play/birth/death/terror/qualitative/research accomplished, if anything. Maybe research play is vital, what keeps us fit to do critical qualitative research. Yet research play moves (well) beyond normative rules of much qualitative research. Is it worth the risk? Can we know? Even after?
Keywords: dept.cur